Timed Artificial Insemination: Pregnancy Rates in Sokoto Gudali Cattle Treated with Prostaglandin F2 Alpha at a Private Dairy Farm in Nigeria. - Leigh, Olufisayo Oluwadamilare; Mustapha, Lukman; Linda, Agbugba Chinyere; Ibiam, Adaeze Ezenwanyi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
Pregnancy rates (PR) resulting from timed artificial insemination (TAI) with frozen semen were investigated in 192 Sokoto Gudali (SG) cattle following estrus synchronization under 11- and 12- day treatment intervals with prostaglandin F2 alpha (Estrumate®). Two-point inseminations at 60 h and 72 h post Estrumate® treatments were used. All cattle were randomly allocated to 2 groups i.e. A and B, such that each sub-group of A1, A2, B1 and B2 had sixteen (16) cows and thirty two (32) heifers. Furthermore, cattle in Groups A and B were administered double Estrumate® injections at 11- and 12-day intervals, respectively. Cattle in sub-groups A1 and B1 were inseminated at 60 h post second Estrumate® injection while A2 and B2 were inseminated at 72 h. Pregnancy was diagnosed using the 60-day non return to estrus and confirmed via rectal palpation at 90 days post insemination. The results showed the following PR: 33%, 83%, 33% and 33% for cattle in sub-groups A1, A2, B1 and B2, respectively. It is concluded therefore that timed artificial insemination at 72 h in SG cattle treated with double Estrumate® injections at 11-day interval produced the best pregnancy rate. These findings raises hope on the future application of TAI in breeding the SG cattle with prostaglandin F2 alpha as single agent of estrus synchronization.